Dispute Resolution in User Agreement on Cryptocurrency Sales Platform That Are Not Based on Indonesian Legislation - Zahra, Tifani Haura; Suparto, Susilowati; Muchtar, Helitha Novianty (Media Hukum Indonesia (MHI), 2024)
Dispute resolution arrangements in the field of physical trading of crypto assets must comply with BAPPEBTI Regulation No. 8 of 2021 in order to be harmonized and have strong legal certainty. However, in practice there is a dispute resolution clause on the crypto asset exchange platform that is not in accordance with BAPPEBTI Regulation No. 8 of 2021. This study aims to determine the dispute resolution chosen based on the agreement in the user agreement on the cryptocurrency sales platform that is not based on BAPPEBTI Regulation No. 8 of 2021 and the legal force of the decision issued by the institution chosen based on the dispute resolution agreement in the user agreement in the field of physical trading of crypto assets. This research uses a research method with a normative juridical approach. The specification of the research conducted is descriptive analysis. The stages of this research focus on literature research and conduct field studies by conducting interviews. Based on the research results, two things can be concluded. First, the dispute resolution chosen based on the agreement in the crypto asset physical trading user agreement that is not based on BAPPEBTI Regulation No. 8 of 2021, the agreement remains binding on both parties as law for the parties. However, the crypto asset exchange platform is considered non-compliant with BAPPEBTI Regulation No. 8 of 2021 and may be subject to administrative sanctions. Second, the legal force related to the decision issued by the institution chosen based on the dispute resolution agreement in the user agreement in the field of physical trading of crypto assets and not in accordance with BAPPEBTI Regulation No. 8 of 2021 is final, binding, and has permanent legal force because the dispute resolution has been agreed by both parties in the user agreement before the dispute occurs (pactum de compromittedo).